Internalisasi Nilai-Nilai Aswaja dalam Organisasi IPNU IPPNU Pimpinan Anak Cabang (PAC) Sempor - Amaril Kholifah Fibrianti; Fikria Najitama; Agus Nur Soleh (IAINU Kebumen, 2023)
The purpose of this thesis research is to find out how the process of internalizing aswaja values in the IPNU IPPNU PAC Sempor organization is carried out. As well as knowing about the obstacles and solutions faced in the process of internalizing the values of aswaja in the IPNU IPPNU PAC Sempor organization. Data collection methods in this study were using observation, interviews, and documentation. The data analysis technique in this research is using qualitative analysis in the from of description, namely a description of an activity. The result of this research is the process of internalizing aswaja values in the IPNU IPPNU PAC Sempor organization through stages, namely the aswaja knowing stage, aswaja feeling, and aswaja action. While the obstacles faced in the processof internalizing the values of aswaja in the IPNU IPPNU PAC Sempor organization include the lack of quality knowledge of each individual or cadre, parental permission, geographical location, and the existence of concurrent activities.